THE EFFECT OF CONSUMER PERCEPTION ON PRODUCT IMAGE ADVERTISED ON YOUTUBE - Elida, Dini; Ermawati, Eka (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: The purpose of this study is to describe consumers' perceptions of YouTube commercials and to examine the impact of consumer perception on the product image. Online media aids in the efficient or wider reach of advertisements. However, several studies have found that consumers are upset by video commercials and thus use skip ad features. The disparity between consumer perceptions of YouTube ads and marketer perceptions of Youtube ads may result in unproductive marketer advertising decisions when selecting the YouTube platform. Methods: According to Dharmasraya Central Statistic Department data, the research population is Youtube users who live in four districts with a total population of 120.979 persons. Non-probability sampling was used to determine the research sample. Using Isaac and Michael's sampling formula, the sample size is 347 people. Product image is the dependent variable, and the independent factors are irritation, informativeness, and purchase. To collect data, valid and reliable questionnaires with a five-stage Likert scale were employed, and SPSS 20.0 was used to assess the study hypotheses. Results: The results demonstrate that customer impression of irritation toward YouTube advertisements has little effect on the product image, however informativeness of YouTube ads and purchase have a substantial effect on the product image. Variable independence has a large and simultaneous impact on the product image. Conclusion and suggestion: This finding indicates that respondent perceptions of how informative YouTube commercials are and their product purchase experiences based on YouTube ads have a favorable and significant impact on product images displayed on YouTube. Other findings show that regardless of how frequently respondents skip YouTube.